Radical and Environmentally Friendly Route to Poly(fullerene)s Incorporating C60, C70, and PCBM - Batagianni, Eleftheria; Doat, Olivier; Elissalt, Nicolas; Moungadji Bouassa, Douvotsu Elisa; Bittencourt, Jessyka Carolina [UNESP]; Cardoso Goncalves, Gabriel; Fernandes Moreno, Vitor [UNESP]; Morais Lima, João Victor [UNESP]; Nogueira, Gabriel Leonardo [UNESP]; Affonço, Lucas Jorge [UNESP]; Paulin, João Vitor [UNESP]; Fernandes, Silvia Leticia [UNESP]; et al. (American Chemical Society (ACS), 2025)
For the first time, this article shows how it is possible to make well-soluble poly(fullerene xylene)s using potassium iodide and in low amounts of solvents. This new method makes it possible to use low-cost, environmentally friendly starting materials, nonchlorinated solvents, and main-chain C60, PCBM, and for the first time, C70, polymers. The reaction can even be performed in the presence of water, further increasing its environmental friendliness. Specifically, a dibromomethylated comonomer, such as 2,5-bis(bromomethyl)-1,4-bis(oxidodecyl)benzene, is reacted with potassium iodide, 18-crown-6, and fullerene in refluxing toluene to yield highly modular alternating copolymers. Model reactions show that polymerization works by the transformation of methylene bromides into methylene iodides, which then disintegrate to make methylene radicals that react with the fullerenes. The radical nature of this new iodine-mediated polymerization (IMP) is confirmed by its sensitivity to the radical trap (2,2,6,6-tetramethylpiperidin-1-yl)oxyl (TEMPO). The comonomers add in pairs to the fullerene to yield linear chains. NMR and UV-visible spectroscopy along with quantum calculations suggest that most bonds to the fullerene are in 1,4-positions on the same hexagonal ring, however, a minority of C60-methylene bonds are situated several bonds apart on the fullerene, suggesting that iodine “walks” across the fullerene surface. This new polymerization of fullerene, without its reliance on copper and chlorinated solvents and ability to work in the presence of water, makes it of wide use for materials for optoelectronics and medicine where even trace impurities can impact heavily on material properties.